Cognitive Behavior Therapy as Relapse Prevention for Opioid Use Disorders : Cognitive Behavior Therapy for Opioid Use Disorders - Shahzadi, Mafia; Jabeen, Mehwish; Unbrin, Aqila; Ul-Ain, Qurat; Amin, Zobia (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Opioid use disorder (OUD) is a prevailing psychiatric illness that provides foundations of morbidity and mortality. Objective: To investigate the effectiveness of Cognitive Behavior Therapy (CBT) in terms of relapse prevention in the treatment of patients with opioid use disorders. Methods: After the period of detoxification, an individualized treatment plan was made based on CBT. To assess the effectiveness of planned and executed CBT sessions, pre and post assessment method was opted. Results: Results specify that CBT worked successfully as relapse prevention in one-on-one sessions. CBT attested to be working in treating patients' lapses as well as relapses by increasing control on cravings and improving assertive behavior. Conclusions: The conclusion can be drawn that CBT is an effective methodology that successfully deals with patients' cravings, and develops assertive behavior thereby preventing relapse.